Cultivating Language Confidence in Primary Learners: The Synergy of Picture Story Media and Bandura’s Self-Efficacy in Regional Language Pedagogy - Prahastiwi , Eka Danik; Minsih, Minsih; Muhammad , Siti Norlina (Jurnal Pendidikan Anak, 2025)
Javanese language learning in schools base face various challenges , especially low interest Study students and lack of trust self in use Language area . Research This aim For analyze effectiveness use of storytelling media illustrated in increase ability Javanese language and student self-efficacy based on Bandura's theory . Research use quasi-experimental type design one-group pretest–posttest with involving 10 students class IV in one of the school basis in East Java. The instruments used covering test ability Javanese language and self-efficacy questionnaire developed based on four Bandura's sources of self-efficacy. Research results show existence improvement significant on ability language and students' self-efficacy levels after learning using story media illustrated , which is proven through paired t-test results (p < 0.05). Story media illustrated give contribution through mastery experiences , vicarious experiences , verbal persuasion , as well as improvement condition emotional positive students . Findings This strengthen relevance Bandura's theory in context learning Language area and emphasized that the story media illustrated is an effective , interesting and capable learning strategy build trust self students . Research This give implications important for teachers and developers curriculum in increase quality Javanese language learning in schools base